Dampak Pelanggaran Kode Etik Profesi Akuntan Publik Terhadap Profesionalisme Akuntan - Muhammad Suhal; Andreas Bambang Daryatno (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The purposes of this study to analyses the impact of professional code violations on the level of professionalism of public accountants in Indonesia. Professional ethics are the moral and social foundation for maintaining public trust in financial reports. Code violations such as financial statement manipulation, corruption, conflicts of interest, and breaches of independence due to strong internal pressure to achieve certain targets to maintain reputation in the eyes of stakeholders, cause a decline in the integrity and reputation of the profession. Problems of governance and fraud at the client management level, weak internal controls, weaknesses in professional skepticism and audit procedures, and poor-quality control within public accounting firms pose challenges for accountants. This research uses a cumulative descriptive research design that departs from previous case studies. According to Sugiyono (2020), descriptive research aims to provide a clear picture of a particular condition, phenomenon, or event in a systematic and measurable manner. Meanwhile, a cumulative approach allows for the collection and analysis of data from various sources and previous studies on an ongoing basis. The research sample is a case study of several large companies in Indonesia, including PT Pertamina (Persero), PT Timah Tbk, PT Garuda Indonesia Tbk, PT Asuransi Jiwasraya (Persero), PT Indofarma Tbk, PT Sunprima Nusantara Pembiayaan (SNP Finance), and PT eFishery. The results of the study indicate that ethical violations directly impact state losses and a decline in accountant professionalism, reducing investor confidence and damaging the image of the public accounting profession. Therefore, stricter enforcement of professional ethics and improved ethics training are necessary so that public accountants can maintain their integrity and credibility.